2009
DOI: 10.1007/s12665-009-0284-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of phosphorus bioavailability in sediments of the shallow lakes in the middle and lower reaches of the Yangtze River region, China

Abstract: Phosphorus (P) fractions and their bioavailability in the sediments from the middle and lower reaches of the Yangtze River region were investigated using different chemical extraction methods. The results show that the contents of bioavailable P in the sediments extracted by different extraction procedures varied greatly. But their rank order was similar. Potentially releasable P (PRP) was the largest, followed by algal available P (AAP), NaHCO 3 extractable P (Olsen-P), water soluble P (WSP), and readily deso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Fe/Al–P had a large spatial variation, with higher concentrations at NW corner and the western tip where external pollution from the discharge of wastewater is serious. Some researchers reported that Fe/Al–P concentration in sediments was closely related to the pollution degree , which was also confirmed in this study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Fe/Al–P had a large spatial variation, with higher concentrations at NW corner and the western tip where external pollution from the discharge of wastewater is serious. Some researchers reported that Fe/Al–P concentration in sediments was closely related to the pollution degree , which was also confirmed in this study.…”
Section: Discussionsupporting
confidence: 90%
“…The potential release risk of sediment P in Swan Lake P fractions in sediments can be used to evaluate P bioavailability and release risk for the overlying water at a certain degree [9,10,12]. In Swan Lake, different bioavailable P followed the order: AAP > Olsen-P > WSP > RDP, which was in agreement with the results in other water bodies in China [10,27]. Higher concentrations of WSP, RDP, and Olsen-P were found at the western tip, the SE corner and central area, suggesting that the sediments at these areas had higher P availability for algal growth at present.…”
Section: 3supporting
confidence: 83%
See 1 more Smart Citation
“…Others have reported that the bio-available P extracted from TP mainly correlates with NaOH-P in heavily polluted sediments [41]. Therefore, NaOH-P has been used to estimate both short-and long-term availability of P, which is released for the growth of phytoplankton when anoxic conditions prevail at the water-sediment interface [9,42].…”
Section: Distribution Characteristics Of Metal Oxide-boundmentioning
confidence: 99%
“…Zhou et al (2001) used linear correlation models to characterize the relationship between TP and the four fractions of BAP. Wang et al (2010) found in heavily polluted sediments, that BAP has a significant relationship with TP, NaOH-P and IP. However, this study represents a rare attempt to consider all influence P fractions together into one feasible model and predict BAP fractions and their origin source.…”
Section: Introductionmentioning
confidence: 87%